SPATIAL AND TEMPORAL PATTERNS OF THE MACROBENTHIC ASSEMBLAGES IN RELATION TO ENVIRONMENTAL VARIABLES - Sapto P Putro (JOURNAL OF COASTAL DEVELOPMENT, 2007)
This study focuses on the effect of fallowing of southern blue-fin tuna farms in southern Spencer Gulf, South Australia, on macrobenthic assemblage comparing spatial and temporal patterns of distribution and abundance at eight control sites and eight fallowed pontoon sites, during the period October 2002 to October 2003. Two stations at each site were sampled five times throughout the year with four replicates. Polychaetes were the most abundant organisms both at control sites (76.4%) and fallowed pontoon sites (80.5%). Five dominant taxa (Capitellidae, Cirratullidae, Lumbrineridae, Nephtyidae, and Spionidae), relatively tolerant to organic enrichment, were generally recorded in higher numbers at the fallowed sites than at control sites.Assessed using univariate and multivariate analyses, a significant difference in abundance between the control and fallowed pontoon sites was found, which also showed a significant effect of time. A slight decreased in diversity, number of taxa, and evenness at fallowed pontoon sites compared to those at control sites was observed. Seasonal fluctuations caused by natural variability, especially hydrodynamic conditions and sediment characteristics, are likely to be responsible for the observed changes of the assemblages.